(untitled) (Research, Society and Development, 2024)
The use of seaweed extracts in agriculture, mainly Ascophyllum nodosum, constitutes an ecologically correct alternative to the use of biofertilizer. Although there is great importance in plant development, little research describes information about the effect, influence, agronomic efficiency and economic forecast on the quality of tomato seedlings. The objective of this research was to study the effect of different doses of biofertilizer based on Ascophyllum nodosum seaweed applied in fertigation on the development of seedlings of tomato cultivar Bartô. Experimental research was carried out in the field and, of a quantitative nature, in which a very randomized design was provided, with four treatments (dose of biofertilizer in fertigation: 0 ml L-1, 3 ml L-1, 6 ml L-1 and 9 ml L-1) and four repetitions. Each plot was represented by 10 tomato plants of the Bartô cultivar (Feltrin®). The following characteristics were evaluated: number of leaves, seedling height, stem diameter, root length, fresh mass of the aerial part and fresh mass of the root system. Under the conditions of the experiment, the application of Ascophyllum nodosum (L.) seaweed extract in its different concentrations did not significantly influence the development of tomato seedlings for the evaluated variety, with no better dose found.